Determinan Perdagangan Internasional Karet Indonesia dan Produk Turunannya dengan Negara Mitra Utama: Pendekatan Gravity M - Rossa Putri Hanny (LPPM Universitas Malikussaleh - Indonesia, 2026)
This study aims to analyze the factors influencing Indonesia’s international rubber trade with its main partner countries using the Gravity Model approach. This model assumes that the volume of trade between countries is affected by economic size (GDP), geographical distance, exchange rates, as well as historical and institutional factors. Panel data covering the period from 2005 to 2023 is used, involving 15 major trading partners, including China, the United States, Japan, and ASEAN countries. The estimation results show that the model has strong explanatory power, with a coefficient of determination (R²) of 0.7987. The GDP of partner countries has a positive and significant effect on Indonesia’s rubber exports, indicating that the economic capacity of importing countries strongly determines the demand for this primary commodity. The exchange rate also shows a positive and significant influence, suggesting that rupiah depreciation enhances the competitiveness of Indonesia’s rubber exports. In contrast, Indonesia’s own GDP, geographic distance, RTA, official language, and colonial ties do not have a significant effect on trade volume. However, the contiguity variable is significantly positive, highlighting the importance of physical proximity in improving logistics efficiency and distribution. These findings indicate that Indonesia’s rubber export strategy should emphasize external economic factors and logistics efficiency, rather than relying solely on historical ties. This study offers policy implications to strengthen export competitiveness through exchange rate management and strategic partner mapping.